EFFECT OF IRRIGATION AND MULCHING ON GROWTH AND PRODUCTIVITY OF TURMERIC (Curcuma longa L.) - AMIT KAMBOJ AND BALWINDER SINGH DHILLON (The Bioscan, 2021)
Two irrigation intervals viz., 6 and 12 days under four levels of mulching viz., 0, 5, 10 and 15 t/ha in turmeric were evaluated. The results showed that the highest plant growth viz., plant height (79.6 cm), leaf length (41.0 cm), leaf breadth (12.1 cm) and leaf area (465.6 cm 2 ) and rhizome length (7.90 cm) was recorded in irrigation intervals of 6 days which was significantly higher over the irrigation intervals of 12 days at harvest. The growing of turmeric crop with irrigation every 6 days of the interval is best for better growth and rhizome yield (157.5 q/ ha). Irrigation interval of 6 days (157.5 q/ha) recorded 32.0% higher rhizome yield than 12 days irrigation intervals (119.3 q/ha). The application of straw mulch @ 15 t ha -1 was found to be beneficial and can be practiced for maximizing the yield (214.3 q/ha) of turmeric crop and conserving soil moisture. Mulching @ 5, 10 and 15 t/ha recorded 68.4, 139.5 and 220.8%, respectively, higher rhizome yield than control (no mulch application).